FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERBANKAN SYARIAH DI INDONESIA DAN MALAYSIA - Nisrina Widayuni; Puji Harto (Diponegoro Journal of Accounting, 2014)
In Islamic banks, the disclosure aspect of corporate social responsibility is a form of obedience to Islamic law because it shows the benefits that the company provides to its environment. Accordingly, this study aims to determine the factors that may affect the disclosure of corporate social responsibility (CSR) in Islamic banks in Indonesia and Malaysia. The factors that used in this study are the number of sharia supervisory board meeting, the number of sharia supervisory board members, profitability, leverage and firm size. This study used 36 annual reports of Islamic banks in Indonesia and Malaysia in the period 2010-2012 as samples. The samples are obtained using a purposive sampling method. The measurement of corporate social responsibility disclosure using an index with 32 aspects of the disclosure of which is a replication of the research from Maali et al. (2003). Beside of that,the variables in this study tested using the multiple regression analysis with SmartPLS. From this study we can see that the disclosure of corporate social responsibility on Islamic banking both in Indonesia and Malaysia are quite low. The results showed that profitability has a positive effect, while leverage has a negative effect on the level of disclosure of corporate social responsibility. Meanwhile, the number of sharia supervisory board meetings , the number of sharia supervisory board members and the size of the company do not have a significant effect .